Role of irisin in physiology and pathology - Liu, Shiqiang; Cui, Fengqi; Ning, Kaiting; Wang, Zhen; Fu, Pengyu; Wang, Dongen; Xu, Huiyun (Frontiers in Endocrinology, 2022)
Irisin, out-membrane part of fibronectin type III domain–containing 5 protein (FNDC5), was activated by Peroxisome proliferator-activated receptor γ (PPARγ) coactivator-1α (PGC-1α) during physical exercise in skeletal muscle tissues. Most studies have reported that the concentration of irisin is highly associated with health status. For instance, the level of irisin is significantly lower in patients with obesity, osteoporosis/fractures, muscle atrophy, Alzheimer’s disease, and cardiovascular diseases (CVDs) but higher in patients with cancer. Irisin can bind to its receptor integrin αV/β5 to induce browning of white fat, maintain glucose stability, keep bone homeostasis, and alleviate cardiac injury. However, it is unclear whether it works by directly binding to its receptors to regulate muscle regeneration, promote neurogenesis, keep liver glucose homeostasis, and inhibit cancer development. Supplementation of recombinant irisin or exercise-activated irisin might be a successful strategy to fight obesity, osteoporosis, muscle atrophy, liver injury, and CVDs in one go. Here, we summarize the publications of FNDC5/irisin from PubMed/Medline, Scopus, and Web of Science until March 2022, and we review the role of FNDC5/irisin in physiology and pathology.